Deletions in the KAP6-1 gene are associated with fiber traits in cashmere-producing goats. Issue 6 (18th November 2022) - Zhao, Jin; Ding, Qiang; Li, Lan; Kalds, Peter; Zhou, Shiwei; Sun, Jiayuan; Huang, Shuhong; Wang, Xiaolong; Chen, Yulin
Abstract: Keratin-associated proteins (KAPs) are important structural components of fibers that predominantly present in the ortho-cortex. These proteins form a cross-linked network with keratin intermediate filaments (KIFs), thus producing a strong hair shaft. The keratin-associated protein 6-1 gene ( KAP6-1 ) is a member of the KAPs family that has a potential correlation with fiber traits. In this study, we investigated the influence of KAP6-1 sequence polymorphisms on the fiber characteristics of a Chinese cashmere-producing goat breed ( n  = 844). Two main variants were found, including a three base pair (bp) deletion (namely B) and a 36-bp deletion (namely C), while the reference genotype of KAP6-1 was named A. Among them, the B variant was first reported on cashmere goats. This study then correlated these genotypes with the collected fiber data to investigate the potential association of these variants. The results showed that variant A is associated with decreased fiber diameter ( p  < 0.01), while variant C is associated with deceased fiber length ( p  < 0.01). These two related variants of the KAP6-1 gene have potential applications as gene-makers to improve the fiber diameter and length in cashmere-producing goats.